Colonial and Neocolonial Domination and Alienation: Consequences and Strategies of Resistance in Ngugi Wa Thiong’o’s and Mecere Githae Mugo’s the Trial of Dedan Kimathi (1976) - Babacar Diakhaté (Britain International for Academic Research (BIAR) Publisher, 2021)
Many African political officials have become famous for their political actions, determination, and strong commitment against colonialism, imperialism and even neo-colonialism. In Kenya, Ngugi WA Thiong’o and Mecere Githae Mugo fictionalize the story of Dedan Kimathi. The Trial of Dedan Kimathi (1976) retraces the life of the hero, Kimathi, who leads the Mau Mau movement against British colonizers. Kimathi is imprisoned because of his own brother Wambararia who betrays his people to become free. Whites’ collaborators and neo-colonial actors such as politicians, Business executives and the Church do not succeed to persuade Kimathi to accept the collaborationist option and stop the struggle.